Fast Way to Quality - Stanislav Kmet; Pavol Magner (Communications - Scientific letters of the University of Zilina, 1999)
Every age has its popular words - today, these are quality and information. Information systems are growing everywhere around us. These information activities bring profit to companies.Let’s search for optimal information behaviour. The licensed software ISOxPERT accessible on our market is able to secure the information about the market, competitors, subsuppliers, products and services.